Еstablishing the Central Asian Nuclear-Weapon-Free Zone Is a Step Towards Global Nuclear Security - S. M. Adilkhodzhaeva (Сравнительная политика, 2016)
The article is devoted to an actual problem of guaranteeing global security and promoting an idea of nuclear-free world. The article provides some data on the history of establishing, the key stages of formation and consolidation of international legal agreements of the Central Asian nuclear-weapon-free zone. The author considers peculiarities and distinguishing features of a nuclear-free zone in Central Asia.